Uji Aktivitas Ekstrak Etanol Daun Tembelekan (L.camara L.) terhadap Pertumbuhan Bakteri Salmonella typhi - Ulilta Muktadira; Satrio Wicaksono; Hartati Hartati (Halu Oleo University, 2018)
Background: Infectious diseases are the prime reason of high morbidity and mortality rate especially in developing countries like Indonesia which is mostly caused by bacteria. One of the plants which can be used as an antibacterial alternative ingredient is tembelekan leaf. Research Purpose: This study aimed to determine the activity of ethanol extract of tembelekan leaf on the growth of S.typhi. Research Method: The research uses post test only control design.Independent variable is the ethanol extract of tembelekan leaf and dependent variable is the inhibition zone of the growth of bacteria. Antibacterial activity was tasted using pitting diffusion method.Chloramphenicolusedas a positive controland aquadest as a negativecontrol. Testing activity by concentration of 12,5%, 10%, 7,5% and 5% in threetimesrepetition. Research result: Ethanol extract of tembelekan leafwith concentration 12,5%, 10% and 7,5% resulted inhibitory zone of the growth of S.typhi, respectively for 6,6 mm, 5,3 mm and 2,6 mm. Conclution:The conclusion of the research was ethanol extract of tembelekan leaf has antibacterial activity against S.typhi.Keywords :tembelekan leaf (L.camara L.), S.typhi, infection